Impact Of Couple Protection Rate On Birth Rate : A Stochastic Linear Regression Model - Singh A.S; Mishra R.N; Mohapatra S.C; Bhardwaj S.D (Wolters Kluwer Medknow Publications, 1992)
Couple Protection Rate is one of the proximate determinants of fertility : Since fertility is affected by a number of socio-cultural and biological factors, an increase in contraceptives acceptance need not necessarily be associated with a decline in fertility. In this paper a stochastic linear regression model is fitted on the year wise (1971- 1985) data of Crude Birth Rate (C.B.R) and Couple Protection Rate (C.P.R) of India. C.B.R. was negatively correlated with sterilization as well as IUD and conventional Contraception (CC). The stochasticity of the model would also be influenced by factors like education and socio- economic condition etc.